The Influence of Social Environment and Parents’ Role on Parenting Self-Efficacy in Child Marriage Couples - Desti Wahyuning; Sugiyo; Awalya (Jurnal Bimbingan Konseling, 2024)
Most child marriage cases somewhat harm the parenting process and self-efficacy. Regarding this issue, the present study examined the impact of social environment and parenting roles on parenting self-efficacy in child marriage couples. A quantitative approach with the ex post facto correlational design was employed by involving 109 respondents residing in two sub-districts in Semarang City. Based on the hierarchical regression test, it was found that (1) the social environment positively predicted parenting self-efficacy, and (2) democratic and permissive parenting styles positively predicted parenting self-efficacy. Thus, it can be concluded that the better the social environment and parenting roles' significance value, the more impact parenting self-efficacy in child marriage couples will have.